2017
DOI: 10.1136/bcr-2017-221969
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration of Nasopore nasal packing

Abstract: We present a case of postoperative Nasopore aspiration in an otherwise fit and well 11-year-old. An endoscopic adenoidectomy had been performed without incident and Nasopore packing placed into each nasal cavity. Immediately after extubation, there was marked hypoxia, tachypnoea and high clinical suspicion of pack aspiration. The patient returned to theatre for emergency rigid bronchoscopy and retrieval of nasal packing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In this case, the biodegradable NasoPore ® was placed loose in the posterior aspect of the nasal cavity close to the choana and dislodged after extubation, resulting in sudden hypoxia and tachypnea. 3 Despite the successful resolution of our case, fatalities have been attributed to NP aspiration. In these cases, NP aspiration occurred during the awakening phase after removal of the tracheal tube.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In this case, the biodegradable NasoPore ® was placed loose in the posterior aspect of the nasal cavity close to the choana and dislodged after extubation, resulting in sudden hypoxia and tachypnea. 3 Despite the successful resolution of our case, fatalities have been attributed to NP aspiration. In these cases, NP aspiration occurred during the awakening phase after removal of the tracheal tube.…”
Section: Discussionmentioning
confidence: 68%
“…Whether a dissolvable material could have been a safer option compared to our chosen NP is debatable considering that aspiration of NasoPore ® has also been described. In this case, the biodegradable NasoPore ® was placed loose in the posterior aspect of the nasal cavity close to the choana and dislodged after extubation, resulting in sudden hypoxia and tachypnea 3 …”
Section: Discussionmentioning
confidence: 99%
“…18 Smith and Reddy reported sudden hypoxia at extubation following accidental aspiration of Nasopore® nasal packing after adenoidectomy, necessitating emergency bronchoscopic retrieval of the pack. 19 Cited by Lovinescu et al a similar account was reported where an aspirated nasal pack accidentally dislodged into left main bronchus during recovery. 20 Unanticipated trigemino-cardiac reflex (naso-pulmonary or Kratschmer reflex) has been reported as a most dreaded potential complication associated with nasal packing, in which trigeminal stimulation from constant pressure eventuates into catastrophic bradycardia, AV block, syncope, bronchospasm, asystole and even death.…”
Section: Discussionmentioning
confidence: 71%